Restructuring Internship in Teaching, SEP and School based Practicum - Srivastava, G. N. Prakash (JOURNAL OF INDIAN EDUCATION, 2019)
Internship is an integral part of professional preparation of a teacher in making. Internship is an arrangement under which a prospective teacher can acquire first hand experience as a teacher in situations closely resembling his professional responsibilities. Milestones in its development are at Brown University programme in 1909, and the University of Cincinnati in 1919. Internship in teaching as visualised by NCERT in 1963 and 1991 has proved opportunities to develop high level of competence in teacher’s work by working full time in the cooperative schools with a wide variety of experiences, and to acquire all necessary skills for the profession. It has three distinct phases viz. pre-internship phase, internship phase and post internship phase. Preinternship phase may inclued school’s observation and training in core teaching compelen cries. During internship phase trainees are to be placed for teachingpractice and involvement in various school activities under some mentors. Post-internship activities may include post-internship seminar and discussion on interns’ (trainees’) performance and sharing of experiences.